Career trajectories of Masters in Education (M.Ed.) students : a tracer study of the M.Ed. class of 1999 at the University of the Witwatersrand. - Sing, Rinel (My University, 2011)
The expansion of higher education and changes in the labour markets seem to have reached a point where training for an M.Ed is affected by a number of issues traditionally raised in the context of graduate employment and work. Growing emphasis is placed on general skills and flexibility, which is briefly mentioned in this report. Labour market theory, human capital development, social capital and career development are explored in detail. Management is no longer perceived in terms of maintaining the business machine but is evolving into a motivator and leader of staff, an inspirational entity that is quintessential to the retention of highly qualified staff . This has resulted in the language of business changing, thus the „efficient company‟ has become a „learning organisation‟ (Germishuys, 2006). Therefore it is of great interest to actually conduct a case study of 11 M.Ed. graduates to track their career trajectories to see where this prestigious qualification has taken them. The researcher traces a general group of M.Ed graduates from the class of 1999 from the University of the Witwatersrand (Wits). The main idea of this study is to ascertain exactly what it is that the sample M.Ed graduates have accomplished in their professional lives. It was found that the colour of one‟s skin, background, contextual factors, opportunities, social networking and career aspirations have played a pivotal role in the career progression of the M.Ed. graduates.
Keywords: Globalisation; Internationalisation; Human capital; Social capital; Labour market; Career development; Employment policy; Career trajectories